5.9.70 Problems 6901 to 7000

Table 5.767: First order ode linear in derivative

#

ODE

Mathematica

Maple

18511

\[ {}t x^{\prime }+x \ln \left (t \right ) = t^{2} \]

18512

\[ {}t x^{\prime }+x g \left (t \right ) = h \left (t \right ) \]

18514

\[ {}x^{\prime } = -\lambda x \]

18532

\[ {}y^{\prime }+c y = a \]

18535

\[ {}y^{\prime } = \frac {\sqrt {1-y^{2}}\, \arcsin \left (y\right )}{x} \]

18537

\[ {}v^{\prime }+u^{2} v = \sin \left (u \right ) \]

18539

\[ {}v^{\prime }+\frac {2 v}{u} = 3 \]

18540

\[ {}\sin \left (x \right ) \cos \left (y\right )^{2}+\cos \left (x \right )^{2} y^{\prime } = 0 \]

18541

\[ {}y^{\prime }+\sqrt {\frac {1-y^{2}}{-x^{2}+1}} = 0 \]

18542

\[ {}-x y^{\prime }+y = b \left (1+x^{2} y^{\prime }\right ) \]

18543

\[ {}x^{\prime } = k \left (A -n x\right ) \left (M -m x\right ) \]

18544

\[ {}y^{\prime } = 1+\frac {1}{x}-\frac {1}{y^{2}+2}-\frac {1}{x \left (y^{2}+2\right )} \]

18545

\[ {}y^{2} = x \left (y-x \right ) y^{\prime } \]

18546

\[ {}2 x^{2} y+y^{3}-x^{3} y^{\prime } = 0 \]

18547

\[ {}2 a x +b y+\left (2 c y+b x +e \right ) y^{\prime } = g \]

18548

\[ {}\sec \left (x \right )^{2} \tan \left (y\right ) y^{\prime }+\sec \left (y\right )^{2} \tan \left (x \right ) = 0 \]

18549

\[ {}x +y y^{\prime } = m y \]

18550

\[ {}\frac {2 x}{y^{3}}+\left (\frac {1}{y^{2}}-\frac {3 x^{2}}{y^{4}}\right ) y^{\prime } = 0 \]

18551

\[ {}\left (T+\frac {1}{\sqrt {t^{2}-T^{2}}}\right ) T^{\prime } = \frac {T}{t \sqrt {t^{2}-T^{2}}}-t \]

18552

\[ {}y^{\prime }+x y = x \]

18553

\[ {}y^{\prime }+\frac {y}{x} = \sin \left (x \right ) \]

18554

\[ {}y^{\prime }+\frac {y}{x} = \frac {\sin \left (x \right )}{y^{3}} \]

18555

\[ {}p^{\prime } = \frac {p+a \,t^{3}-2 p t^{2}}{t \left (-t^{2}+1\right )} \]

18556

\[ {}\left (T \ln \left (t \right )-1\right ) T = t T^{\prime } \]

18557

\[ {}y^{\prime }+y \cos \left (x \right ) = \frac {\sin \left (2 x \right )}{2} \]

18558

\[ {}y-y^{\prime } \cos \left (x \right ) = y^{2} \cos \left (x \right ) \left (1-\sin \left (x \right )\right ) \]

18562

\[ {}\sqrt {t^{2}+T} = T^{\prime } \]

18564

\[ {}y^{\prime } = \left (x +y\right )^{2} \]

18566

\[ {}\sec \left (\theta \right )^{2} = \frac {m s^{\prime }}{k} \]

18569

\[ {}y^{\prime } = x \left (y^{2} a +b \right ) \]

18570

\[ {}n^{\prime } = \left (n^{2}+1\right ) x \]

18571

\[ {}v^{\prime }+\frac {2 v}{u} = 3 v \]

18572

\[ {}\sqrt {-u^{2}+1}\, v^{\prime } = 2 u \sqrt {1-v^{2}} \]

18574

\[ {}\frac {y^{\prime }}{x} = y \sin \left (x^{2}-1\right )-\frac {2 y}{\sqrt {x}} \]

18575

\[ {}y^{\prime } = 1+\frac {2 y}{x -y} \]

18576

\[ {}v^{\prime }+2 v u = 2 u \]

18577

\[ {}1+v^{2}+\left (u^{2}+1\right ) v v^{\prime } = 0 \]

18578

\[ {}u \ln \left (u \right ) v^{\prime }+\sin \left (v\right )^{2} = 1 \]

18588

\[ {}5 x^{\prime }+x = \sin \left (3 t \right ) \]

18604

\[ {}y^{\prime }+\frac {x y}{x^{2}+1} = \frac {1}{x \left (x^{2}+1\right )} \]

18619

\[ {}y^{\prime }+\frac {y}{x} = -x^{2}+1 \]

18620

\[ {}y^{\prime }+y \cot \left (x \right ) = \csc \left (x \right )^{2} \]

18621

\[ {}y^{\prime } = x -y \]

18622

\[ {}\left (x^{2}+1\right ) y^{\prime }+x^{2} y = x^{3}-x^{2} \arctan \left (x \right ) \]

18623

\[ {}y^{\prime }+\frac {x y}{x^{2}+1} = \frac {1}{x \left (x^{2}+1\right )} \]

18624

\[ {}x \left (-x^{2}+1\right ) y^{\prime }+\left (x^{2}-1\right ) y = x^{3} \]

18625

\[ {}y^{\prime }+y \cos \left (x \right ) = \frac {\sin \left (2 x \right )}{2} \]

18626

\[ {}x \left (-x^{2}+1\right ) y^{\prime }+\left (2 x^{2}-1\right ) y = a \,x^{3} \]

18627

\[ {}y^{\prime }+y \sin \left (x \right ) = y^{2} \sin \left (x \right ) \]

18628

\[ {}\left (-x^{2}+1\right ) y^{\prime }-x y = a x y^{2} \]

18629

\[ {}y^{\prime }+y \cos \left (x \right ) = y^{n} \sin \left (2 x \right ) \]

18630

\[ {}3 y^{\prime } y^{2}+y^{3} = x -1 \]

18631

\[ {}y^{\prime }-y \tan \left (x \right ) = y^{4} \sec \left (x \right ) \]

18632

\[ {}y \sqrt {x^{2}-1}+x \sqrt {y^{2}-1}\, y^{\prime } = 0 \]

18633

\[ {}\left ({\mathrm e}^{y}+1\right ) \cos \left (x \right )+{\mathrm e}^{y} \sin \left (x \right ) y^{\prime } = 0 \]

18634

\[ {}\sqrt {2 a y-y^{2}}\, \csc \left (x \right )+y \tan \left (x \right ) y^{\prime } = 0 \]

18635

\[ {}y \left (3+y\right ) y^{\prime } = x \left (3+2 y\right ) \]

18636

\[ {}x^{3}-3 x^{2} y+5 x y^{2}-7 y^{3}+\left (y^{4}+2 y^{2}-x^{3}+5 x^{2} y-21 x y^{2}\right ) y^{\prime } = 0 \]

18637

\[ {}x^{3}+4 x y+y^{2}+\left (2 x^{2}+2 x y+4 y^{3}\right ) y^{\prime } = 0 \]

18638

\[ {}\sin \left (x \right ) \cos \left (y\right )+\cos \left (x \right ) \sin \left (y\right ) y^{\prime } = 0 \]

18639

\[ {}x^{2}+\ln \left (y\right )+\frac {x y^{\prime }}{y} = 0 \]

18640

\[ {}x \left (x -2 y\right ) y^{\prime }+2 y^{2}+x^{2} = 0 \]

18641

\[ {}5 x y y^{\prime }-x^{2}-y^{2} = 0 \]

18642

\[ {}\left (x^{2}+3 x y-y^{2}\right ) y^{\prime }-3 y^{2} = 0 \]

18643

\[ {}\left (x^{2}+2 x y\right ) y^{\prime }-3 x^{2}+2 x y-y^{2} = 0 \]

18644

\[ {}5 x y y^{\prime }-4 x^{2}-y^{2} = 0 \]

18645

\[ {}\left (x^{2}-2 x y\right ) y^{\prime }+x^{2}-3 x y+2 y^{2} = 0 \]

18646

\[ {}3 x^{2} y^{\prime }+2 x^{2}-3 y^{2} = 0 \]

18647

\[ {}\left (3 x +2 y-7\right ) y^{\prime } = 2 x -3 y+6 \]

18648

\[ {}\left (6 x -5 y+4\right ) y^{\prime } = 2 x -y+1 \]

18649

\[ {}\left (5 x -2 y+7\right ) y^{\prime } = x -3 y+2 \]

18650

\[ {}\left (x -3 y+4\right ) y^{\prime } = 5 x -7 y \]

18651

\[ {}\left (x -3 y+4\right ) y^{\prime } = 2 x -6 y+7 \]

18652

\[ {}\left (5 x -2 y+7\right ) y^{\prime } = 10 x -4 y+6 \]

18653

\[ {}\left (2 x -2 y+5\right ) y^{\prime } = x -y+3 \]

18654

\[ {}\left (6 x -4 y+1\right ) y^{\prime } = 3 x -2 y+1 \]

18727

\[ {}\left (1-x \right ) y^{\prime }-1-y = 0 \]

18728

\[ {}y^{\prime }+\sqrt {\frac {1-y^{2}}{-x^{2}+1}} = 0 \]

18729

\[ {}-x y^{\prime }+y = a \left (y^{2}+y^{\prime }\right ) \]

18730

\[ {}3 \,{\mathrm e}^{x} \tan \left (y\right )+\left (1-{\mathrm e}^{x}\right ) \sec \left (y\right )^{2} y^{\prime } = 0 \]

18731

\[ {}x^{2}+y^{2}-2 x y y^{\prime } = 0 \]

18732

\[ {}y^{2}+\left (x y+x^{2}\right ) y^{\prime } = 0 \]

18733

\[ {}x^{2} y-\left (y^{3}+x^{3}\right ) y^{\prime } = 0 \]

18734

\[ {}\left (4 y+3 x \right ) y^{\prime }+y-2 x = 0 \]

18735

\[ {}3 y-7 x +7+\left (7 y-3 x +3\right ) y^{\prime } = 0 \]

18736

\[ {}\left (y-3 x +3\right ) y^{\prime } = 2 y-x -4 \]

18737

\[ {}x^{2}-4 x y-2 y^{2}+\left (y^{2}-4 x y-2 x^{2}\right ) y^{\prime } = 0 \]

18738

\[ {}x +y y^{\prime }+\frac {x y^{\prime }-y}{x^{2}+y^{2}} = 0 \]

18739

\[ {}a^{2}-2 x y-y^{2}-\left (x +y\right )^{2} y^{\prime } = 0 \]

18740

\[ {}2 a x +b y+g +\left (2 c y+b x +e \right ) y^{\prime } = 0 \]

18741

\[ {}\left (2 x^{2} y+4 x^{3}-12 x y^{2}+3 y^{2}-x \,{\mathrm e}^{y}+{\mathrm e}^{2 x}\right ) y^{\prime }+12 x^{2} y+2 x y^{2}+4 x^{3}-4 y^{3}+2 y \,{\mathrm e}^{2 x}-{\mathrm e}^{y} = 0 \]

18742

\[ {}y-x y^{\prime }+\ln \left (x \right ) = 0 \]

18743

\[ {}\left (x y+1\right ) y-\left (1-x y\right ) x y^{\prime } = 0 \]

18744

\[ {}a \left (x y^{\prime }+2 y\right ) = x y y^{\prime } \]

18745

\[ {}x^{4} {\mathrm e}^{x}-2 m x y^{2}+2 m \,x^{2} y y^{\prime } = 0 \]

18746

\[ {}y \left (2 x y+{\mathrm e}^{x}\right )-{\mathrm e}^{x} y^{\prime } = 0 \]

18747

\[ {}x^{2} y-2 x y^{2}-\left (x^{3}-3 x^{2} y\right ) y^{\prime } = 0 \]

18748

\[ {}y \left (x y+2 x^{2} y^{2}\right )+x \left (x y-x^{2} y^{2}\right ) y^{\prime } = 0 \]

18749

\[ {}x^{2}+y^{2}+2 x +2 y y^{\prime } = 0 \]

18750

\[ {}x^{2}+y^{2}-x^{2} y y^{\prime } = 0 \]